Developing anatomy demonstrators of the future: The role of team-teaching - Hughes, Diane; Whitburn, Laura; Colasante, Meg; McDonald, Aaron; McGowan, Heath; Zacharias, Anita; Green, Rodney (Journal of University Teaching and Learning Practice, 2020)
ABSTRACTRecent decades have seen cadaveric anatomy teaching decline and shift from traditionally team-taught practicals in large dissection laboratories to sole-taught classes in smaller laboratories. Such changes may alter teaching quality due to loss of peer teacher interactions in class. The current study aimed to compare experiences of team-taught versus sole-taught practicals in the same course across two campuses. This paper presents on the staff experiences. The study utilised educational design research methodology for an iterative approach to solving the problem of optimising cadaveric-based teaching. Classes at the metropolitan campus were team-taught (lead demonstrator, clinical demonstrator and near-peer demonstrator, n=18) and sole-taught at the regional, smaller campus (lead demonstrator only, n=5). Demonstrators completed an anonymous online survey that explored their teaching experiences and thematic analysis of survey data was conducted. Benefits of team-teaching were captured under the themes learn-observe-support, more time with students and catering for student differences. While most team-teaching staff reported no challenges, some noted the need for time to establish effective team dynamics. Sole-teaching staff reported the benefit of consistency in teaching but challenges in providing adequate support to all students. While sole-teaching facilitates consistency in teaching, team-teaching enables staff to develop teaching expertise and anatomical knowledge from interactions with a range of demonstrators during practicals. Team-teaching facilitates knowledge transfer between staff, and this holds important workforce implications for developing anatomy teachers of the future.